â€œAnalysis Influence Brand Equity and Service Quality to Costumer Satisfaction Users Blackberry Curve 9300 District Sario Manado â€ - Roring, Ferdy (Universitas Sam Ratulangi, 2012)
Research In Motion (RIM) is the official producer of mobile phones that are currently most popular especially in Indonesia which is the Blackberry. Indonesia is a large market share to Blackberry because of Indonesia's population. 47 percent mobile circulating in Indonesia is Blackberry.The goal of this research is to know the influence of quality of service and brand equity to the satisfaction of consumer users blackberry curve 9300 district Sario the city of manado.In this research, the methods of analysis used is regression analysis method. The population was taken is the blackberry curve 9300 user with samples as much as 100 people. Sampling techniques research using simple random sampling.Research results by using regression analysis showed that partially variable quality of service significantly influential to the variable satisfaction but rather to brand equity, does not affect the consumer's satisfaction. And simultaneously variable quality of service and significant impact on brand equity consumer satisfaction.For the RIM Blackberry mobile phone manufacturers should be as much again to improve the quality of service that is better to consumers so that consumers do not migrate or switch to other parties. More manufacturers to optimize quality of service to the higher customer satisfaction. The RIM also should pay attention to brand equity. If the RIM is not paying attention to the brand equity will be decreased to the level of consumer satisfaction that have an impact on decreasing the level of product sales.Keywords: service quality, brand equity, and customer satisfaction